Reconsidering abdominal drainage after left pancreatectomy: the randomized controlled PANDRA II trial - Kaiser, Jörg; Niesen, Willem; Hinz, Ulf; Diener, Markus K.; Pianka, Frank; Klotz, Rosa; Strobel, Oliver; Mehrabi, Arianeb; Berchtold, Christoph; Müller, Beat P.; Schneider, Martin; Loos, Martin; et al. (Annals of surgery, 2025)
Objective: To evaluate intra-abdominal drainage after left pancreatectomy (LP), as it has been a longstanding practice to mitigate postoperative complications, particularly postoperative pancreatic fistulas. Background: Recent studies challenge the necessity of routine drainage, suggesting potential benefits in omitting drains. Methods: The PANDRA II trial was a randomized controlled noninferiority study conducted at the University Hospital Heidelberg between 2017 and 2023. It compared outcomes between patients undergoing open or minimally invasive LP with and without abdominal drainage. The primary endpoint was overall postoperative morbidity assessed by the Comprehensive Complication Index (CCI). Results: A total of 246 patients were included in the intention-to-treat analysis (125 with drainage, 121 without drainage). The no-drain group demonstrated noninferiority to the drain group in terms of CCI (13.90 ± 16.51 vs 19.43 ± 16.92, P < 0.001 for noninferiority). Moreover, the no-drain group had lower overall complication rates (50.41% vs 78.40%, P < 0.001). Specific complications such as postoperative pancreatic fistula (14.88% vs 20.8%, P = 0.226) and postpancreatectomy hemorrhage (4.96% vs 4.80%, P > 0.999) did not differ significantly between groups. Conclusions: The results of the PANDRA II trial demonstrate that omitting routine abdominal drainage after LP is noninferior to placing routine abdominal drainage regarding morbidity measured by the CCI. Omitting a routine abdominal drainage even led to a significant reduction in the overall complication rate.